Surface greenhouse gas fluxes downwind of a penguin colony in the maritime sub-Antarctic. (December 2015) - Drewer, Julia; Braban, Christine F.; Tang, Y. Sim; Anderson, Margaret; Skiba, Ute M.; Dragosits, Ulrike; Trathan, Phil
Abstract: The relationship between ammonia (NH3 ) concentrations downwind from a penguin colony and local surface greenhouse gas (GHG) fluxes was investigated on the remote sub-Antarctic Bird Island (54°00′S, 38°03′W) during summer 2010 (November and December). A Macaroni penguin ( Eudyptes chrysolophus ) colony (40, 000 pairs) at Goldcrest Point is a large point source of NH3 on the island and a measurement transect of 23 m, 36 m, 70 m, 143 m and 338 m was set up downwind from the colony. Atmospheric NH3 concentrations measured by passive diffusion samplers declined from 23 μg m −3 close to the colony to less than 1 μg m −3 338 m downwind. As increased nitrogen (N) deposition can affect soil carbon (C) and N cycling, it can therefore potentially influence GHG and nitric oxide (NO) emission rates. However, in this study, a clear correlation between surface GHG fluxes and atmospheric NH3 concentrations could not be established. Average fluxes for nitrous oxide (N2 O), methane (CH4 ) and carbon dioxide (CO2 ) over the entire transect and the eight week study period ranged from 7 to 23 μg N2 O–N m −2  h −1,  −5.5–245 μg CH4  m −2  h −1, and CO2 respiration rates averaged 2.2 μmol m −2  s −1 . Laboratory studies using intact soil cores from the transect also did not show any significant correlation between atmospheric NH3 concentrations and N2 O, NO, CH4 emissions or CO2 respiration rates. Overall, fluxes measured in the laboratory study reflected the high variability measured in the field. Large changes in soil depth along the transect, due to the topography of the island, possibly influenced fluxes more than NH3 concentration and seabirds appeared to have a more localised input (e.g. ground nesting birds). However, warmer temperatures might have a large potential to increase GHG fluxes in this ecosystem. This study confirms that GHG fluxes do occur in these ornithogenic ecosystems, however, the scale of the impact remains largely unquantified due to high uncertainties and high spatial variability. Highlights: Net emission of N2 O and mostly positive CH4 fluxes. Temperature potential to increase fluxes. Local wildlife activity driving fluxes rather than gradient from penguin colony.